2011
DOI: 10.1038/ajg.2011.170
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Episodes of Irritable Bowel Syndrome Using Ecological Momentary Assessment

Abstract: Episodes of IBS are associated with greater pain (strongest relationship), bloating, and stress scores, and poorer global well-being. Compared with IBS-D, IBS-C and IBS-M are similar in clinical features. Patients overreport pain and stool frequency by diary compared with EMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 18 publications
2
53
1
Order By: Relevance
“…However, even when using prospective diaries, the timing of when patients record symptoms may be an important variable. In one study IBS patients reported more symptoms on a diary completed at the end of the day as compared to five assessments a day for 14 days [43]. We also limited the number of symptom comparisons we made (activity interference and Composite IBS Symptom Score) to reduce the chance of a type 1 error.…”
Section: Discussionmentioning
confidence: 99%
“…However, even when using prospective diaries, the timing of when patients record symptoms may be an important variable. In one study IBS patients reported more symptoms on a diary completed at the end of the day as compared to five assessments a day for 14 days [43]. We also limited the number of symptom comparisons we made (activity interference and Composite IBS Symptom Score) to reduce the chance of a type 1 error.…”
Section: Discussionmentioning
confidence: 99%
“…Although detailed, the scale doesn’t directly assess abdominal pain frequency when compared to the API. Likely the most accurate scale thus far has been developed by Weinland et al [64]; where patients electronically characterize their pain and associated physical and psychological symptoms during each pain episode – thereby eliminating recall bias. At the time of this study’s inception, such a scale was not available and the API was felt to be the most optimal measure for abdominal pain.…”
Section: Discussionmentioning
confidence: 99%
“…Although this entity were not well studied currently, some studies has reported IBS-M is more similar to IBS-C than IBS-D based on similarities in stool frequency, consistency, psychological symptoms and a higher likelihood of transition between these 2 subtypes longitudinally. 32,33 In the present study, it appears that clinical symptoms of IBS-M tend to more resemble IBS-C than IBS-D. Therefore, there might be a considerable movement from IBS-C to IBS-M, but despite several times' review of medical chart including history of medication such as laxative and antidiarrheal or longitudinal symptom change, 35 IBS-M patients in the present study could not be subclassified into either of IBS-D or IBS-C.…”
Section: Discussionmentioning
confidence: 99%